Use of Gamification Techniques in Science Education: report of an intervention in support of Statistics (Research, Society and Development, 2020)
One of the most common problems in school life has been a lack of motivation, involvement or interest by students. The school context is no longer that of information gathering - since nowadays students have several ways of obtaining information - but to involve students in their teaching-learning process. The present work reports the application of gamification techniques in a class of students of International Relations, by a case study, to support scientific education in the curricular component of Applied Statistics. Although typically the focus of courses in this area is not Science, the course at this institution understands the significance of Scientific Education. There is a perception that the application of these techniques in the activity encourages student involvement.